Bimbingan penggunaan Bahasa Jerman praktis bagi pedagang di Kawasan Wisata Alam Bantimurung Kabupaten Maros - Misnah Mannahali; Nurming Saleh; Hasmawati Hasmawati; Mantasiah Mantasiah (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Maros Regency is one of the districts in SouthSulawesi Province which has natural potential in the form ofbeautiful mountains, beaches, stretches of karst and exoticarchaeological sites. This potential makes this area rich innatural attractions and makes it one of the domestic andinternational tourist destinations. One tourist attraction that isvisited by tourists is Bantimurung natural tourism.Bantimurung tourist area is a prime tourist area in SouthSulawesi. As Bantimurung's mainstay tourist area, it offers avariety of interesting tourist attractions such as a flowingwaterfall, river flow with rocky edges flanked by steep cliffs,flying fox and also interesting is the attraction of butterflieswith various colors. This also caused Bantimurung to beknown internationally with the nickname "The Kingdom ofButterfly. According to BPPS data in 2017, the number offoreign tourists entering South Sulawesi was 1491, 69.88%(1042 visits) dominated by 5 countries, namely England,Germany, Singapore, Malaysia and Japan. Germany is thelargest tourist contributor after Britain and Singapore. Fromthe number of visits, the Maros regency government earns 2.5Million in annual income. The government is optimistic toincrease the revenue by fixing the tourism area both in termsof facilities and its infrastructure and human resources. HumanResources whose potential must be developed are traders ofsouvenirs, culinary and other, so that they can at least sell andoffer their trade in German and can even become local guidesin the tourist area.